Regulatory T Cells and Pro-inflammatory Responses Predominate in Children with Tuberculosis - Whittaker, Elizabeth; Nicol, Mark; Zar, Heather J.; Kampmann, Beate (Frontiers in Immunology, 2017)
Background: Following infection with Mycobacterium tuberculosis (M.tb), children are more susceptible to develop disease, particularly extra-pulmonary disease, than adults. The exact mechanisms required for containment of M.tb are not known but would be important to identify correlates of protection. Objective: To comprehensively analyse key immune responses to mycobacteria between HIV negative children with extrapulmonary TB (EPTB) compared to children with pulmonary TB (PTB) or healthy controls. Methods: Whole blood was stimulated in vitro with mycobacteria for 24 hours or 6 days to induce effector and memory responses. CD4, CD8, gammadelta, regulatory T cells and their related cytokines were measured. Samples of children with TB disease were analysed both at time of diagnosis and at the end of TB treatment to determine if any differences were due to TB disease or an underlying host phenotype. Results: 76 children with TB disease (48 with PTB and 28 with EPTB) and 83 healthy controls were recruited to the study. The frequency of CD4+CD25+CD39+FOXP3+ regulatory T cells and secreted IL10 were significantly higher in children with TB compared to healthy controls. IFNgamma, IL17 and IL22 producing gammadelta T cells, IL22 producing CD4+ T cells and secreted pro-inflammatory cytokines (IFNgamma, IL1beta and TNFalpha) were significantly lower in children with TB disease compared to healthy controls. IFNgamma producing CD4+ T cells and Ki67+ proliferating CD4+ T cells however, were present in equal numbers in both groups. Following treatment, these immune parameters recovered to ‘healthy’ levels or greater in children with PTB, but not those with extrapulmonary TB. Conclusions: In children with TB disease a predominantly immune regulatory state is present. These immune findings do not distinguish between children with PTB and EPTB at the time of diagnosis. Following treatment, these inflammatory responses recover in PTB, suggesting the effect is disease specific rather than due to an underlying host defect.